Static and dynamic analysis of a ladder frame truck chassis - Musa, Ismail (2009)
Truck chassis is a major component in a vehicle system. This work involves static and dynamics analysis to determine the key characteristics of a truck chassis. The static characteristics include identifying location of high stress area and determining the torsion stiffness of the chassis. The dynamic characteristics of truck chassis such as the natural frequency and mode shape were determined by using finite element (FE) method. Experimental modal analysis was carried out to validate the FE models. Modal updating of the truck chassis model was done by adjusting the selective properties such as mass density and Poisson’s ratio. Predicted natural frequency and mode shape were validated against the experimental results. Finally, the modification of the updated FE truck chassis model was proposed to reduce the vibration, improve the strength and optimize the weight of the truck chassis. The major area of concern in the truck chassis was structural resonance at 52 Hz, experienced during the torsional and bending modes. Modifications to shift natural frequencies were proposed by increasing the thickness of the chassis center section by 2 mm and additional stiffener members located at the center of the base plate with a thickness of 10 mm. The overall modifications resulted in the natural frequency shifted by 13 % higher than the original value, increased the torsion stiffness by 25 % and reduced the total deflection by 16 %. The overall weight of the new truck chassis was increased by 7%.